Experiences and challenges implementing Uganda's revised English Literature curriculum: Problematization of colonization - Johnson Ocan (Journal of Social, Humanity, and Education, 2024)
Purpose: This study explores teachers' perspectives and challenges in implementing a competency-based English literature curriculum in Uganda after many years of British hegemony. This reflects on the roles and prestige of the English language as it evolved during colonial and postcolonial schools. Research methodology: The method used in this study focuses on secondary literature to refute the claim that the British forced English into Uganda while extinguishing native tongues. Results: According to the major results of the study, students in Uganda had the opportunity to enroll in kindergarten through university-level schooling, where English was the predominant medium of instruction. Limitations: The study's limitations suggest that, although the British gave English education more attention, they were careful to emphasize that national tongues should not be disregarded in favor of English. Following these investigations, the old English language curriculum has always had a tenuous connection with British political and economic interests in Uganda. Contribution: Regarding the contributions of the study, the overhaul of the curriculum was "overdue," according to Hon. Janet Museveni, Minister of Education, Sports and Science who stated in Parliament that the antiquated curriculum was anti-intellectual and opposed to cultural action. However, it is still challenging to put such a change into practice practically. This treatise simply states an ‘implementation gap,’ which is the difference between the intended and actual implementation of the competency-based curriculum.